Atrial Fibrillation Diagnosis and Management in the 21st Century - Karcıoğlu, Özgür; Karbek Akarca, Funda (IntechOpen, 2022)
Atrial Fibrillation - Diagnosis and Management in the 21st Century provides the most up-to-date information about the most common cardiac arrhythmia in humans, atrial fibrillation. In this rapidly developing field of medicine, the book helps to answer the question, "Which treatment should I choose for which patient?" The book also discusses new drugs, applications and interventions in the field. The 12 chapters are written from a variety of viewpoints by authors who use solid, scientific and contemporary approaches to practical questions.